Vascular Endothelial Growth Factor-C Expression in Servical Squamous Cell Carcinoma of Patients with Neoadjuvant Chemotherapy - Kartikasari, Uswatun Khasanah; Priyanto, Heru; Respati, Supriyadi Hari (Indonesian Journal of Medicine, 2019)
Background: Uterine cervical carcinoma is the most gynecological malignancy in women worldwide. The most common type of cervical carcinoma histology is squamous cell carcinoma and has a better prognosis than adenocarcinoma. Neoadjuvant chemotherapy is the management of early-stage cervical carcinoma before radical hysterectomy is performed. In addition to clinical-pathological factors, biomolecular markers are now being developed and used as parameters for evaluating chemotherapy responses. Vascular Endothelial Growth Factor-C is a VEGF derivative that plays a role in the process of vasculogenesis, limphangiogenesis, and the formation of new lymphatic channels which play an important role in metastasis. This study aimed to examine the effect of Paxus-Carboplatin chemotherapy in decreasing VEGF-C in squamous cell cervical carcinoma tissue.Subjects and Method: This was a quasi experiment study conducted at Department of Obstetrics and Gynecology and Pathology Anatomy Laboratory of Dr. Moewardi Hospital/ Faculty of Medicine, Universitas Sebelas Maret. 25 tissue samples of squamous cell stage IB2-IIA2 cervical carcinoma immunohistochemistry VEGF-C expression was carried out before and after Paxus-Carboplatin chemotherapy was given. The data were analyzed by Wilcoxon test.Results: VEGF-C expression in squamous cell cervical carcinoma tissue after chemotherapy was lower (mean = 4.20) than before chemotherapy (mean = 6.16) and it was statistically significant (p<0.001).Conclusion: Neoadjuvant chemotherapy decreases VEGF-C in squamous cell cervical carcinoma tissue.Correspondence: Uswatun Khasanah Kartikasari. Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta. Mobile: 081391444425. Email: uswatunkk@gmail.comIndonesian Journal of Medicine (2019), 4(1): 40-45https://doi.org/10.26911/theijmed.2019.04.01.07